Priestly Rule. - MacDonald, Nathan (Beihefte Zur Zeitschrift Fur die Alttestamentliche Wissensch ;, 2015)
Prophetic oracles in the books of Isaiah and Ezekiel evidence tensions about the Jerusalem temple and its priesthood in Persian Yehud. MacDonald's Priestly Rule challenges the scholarly consensus about how these texts relate to each other. He demonstrates how important written prophetic oracles were in the early Jewish community and disputes the dominance of a Zadokite priestly family in the Second Temple period.